Conocimiento pedagógico del profesorado de inglés en Chile y su necesidad percibida de actualización - Cisterna Zenteno, Cecilia; Díaz Larenas, Claudio; Boudon Araneda, Javiera; Larenas San Martín, María Edith (Universidad de Costa Rica, 2019)
The current paper is a non experimental and cross-sectional research study conducted in the province of Concepción, Chile, and its main aim was to identify the perceptions a group of English teachers hold about their knowledge of English teaching, learning and assessment and their need to update these areas. This research emerges as a diagnostic assessment for the creation of didactic videos aimed at supporting the weakest methodological areas detected among the teachers in the province. Eighty teachers, working mostly in rural areas, were surveyed using a Likert-like scale. The findings show that, in general terms, teachers have a high level of knowledge regarding their teaching areas; however, they also show a great desire to update it. As a conclusion, the surveyed professionals demonstrate a serious commitment to the teaching profession and want, therefore, to improve themselves, even though they have a high level of knowledge in most of the areas consulted. Nevertheless, it is observed that the participants show little knowledge in the area of special educational needs. The use of didactic videos would then contribute to improve their pedagogical competences in those weakest areas.